Design Enhancement of Hose Rolling Tool for Firefighters Using DFMA - Mahmood, Salwa; Zailani, Adam Danial; Nawawi, Azli; Abdul Rahman, Ismail (Journal of Advanced Industrial Technology and Application, 2025)
Firefighting operations depend significantly on effective equipment, with hose rolling tools being crucial for the swift deployment and recovery of fire hoses. Existing hose roller designs frequently exhibit significant component counts, intricate assembly, and elevated manufacturing costs, which hinder operational efficiency and escalate manufacture expenses. This project seeks to improve the design of a hose rolling tool for firefighters by utilizing Design for Manufacturing and Assembly (DFMA) principles to decrease part complexity and cost. The project entailed evaluating the current hose roller design, highlighting inefficiencies, and methodically improving the tool through SolidWorks modelling and manual Design for Assembly (DFA) analysis. Comparative evaluations were performed to analyze part quantity, material expenses, and assembly durations between the original and revised models. The findings indicated a substantial decrease in total components (from 40 to 25), an 11% reduction in production expenses, and a 48% enhancement in assembly efficiency. These findings underscore the efficacy of DFMA in enhancing product design for manufacturing and assembly, resulting in more economical and user-centric firefighting equipment. In summary, the implementation of DFMA principles significantly enhanced the manufacturability and operational efficacy of the hose rolling tool, offering a viable framework for future advancements in firefighting equipment.